2020
DOI: 10.3390/horticulturae6010007
|View full text |Cite
|
Sign up to set email alerts
|

Quality, Yield, and Biomass Efficacy of Several Hydroponic Lettuce (Lactuca sativa L.) Cultivars in Response to High Pressure Sodium Lights or Light Emitting Diodes for Greenhouse Supplemental Lighting

Abstract: Lettuce is an economically important crop that can be grown either in the field or greenhouse. Different challenges are present in either environment; therefore, cultivar selection is important. For hydroponic greenhouse lettuce there is relatively little published information on cultivar selection under different lighting sources. The objective of phase 1 was to determine the influence of lighting using high pressure sodium (HPS) or light emitting diodes (LED) on plant fresh weight, height, tip burn index, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…Our power consumption results and thus the potential of LEDs for reducing energy costs coincide with numerous studies and reviews [ 6 , 9 , 59 ], stating energy reductions up to 70% compared to traditional light sources while producing similar crop yields at equal light intensities, and confirm the current trend of LEDs’ increasing photon efficiencies: While HPS and LED fixtures had nearly identical photon efficiencies until ~2015 [ 6 , 35 ], the best evaluated LED fixture was 40% more photon-efficient than HPS due to technological improvements of LEDs within the PAR region soon after [ 35 , 59 ]. A current study by Hernandez et al (2020) confirms the corresponding increase in biomass efficacy of LEDs, as their LED treatment led to a 2.4 to 3.1 times greater biomass efficacy than HPS, which matches our findings [ 60 ]. Another study in which LED and FL treatments were compared, reported a biomass efficacy three to five times higher under LED than under FL lighting [ 61 ].…”
Section: Resultssupporting
confidence: 91%
“…Our power consumption results and thus the potential of LEDs for reducing energy costs coincide with numerous studies and reviews [ 6 , 9 , 59 ], stating energy reductions up to 70% compared to traditional light sources while producing similar crop yields at equal light intensities, and confirm the current trend of LEDs’ increasing photon efficiencies: While HPS and LED fixtures had nearly identical photon efficiencies until ~2015 [ 6 , 35 ], the best evaluated LED fixture was 40% more photon-efficient than HPS due to technological improvements of LEDs within the PAR region soon after [ 35 , 59 ]. A current study by Hernandez et al (2020) confirms the corresponding increase in biomass efficacy of LEDs, as their LED treatment led to a 2.4 to 3.1 times greater biomass efficacy than HPS, which matches our findings [ 60 ]. Another study in which LED and FL treatments were compared, reported a biomass efficacy three to five times higher under LED than under FL lighting [ 61 ].…”
Section: Resultssupporting
confidence: 91%
“…Decreasing the blue fraction from 20% to 4% resulted in a 12.3% increase in dry mass yield, while increasing the efficacy from 1.72 to 2.51 μmol J -1 resulted in a 27% increase in yield per dollar of electricity. Similar results were reported for 13 lettuce cultivars grown in greenhouses supplemented with HPS or LED lights [23].…”
Section: Fixture Design and Efficacysupporting
confidence: 86%
“…Snowden et al [19] saw little to no effect on morphology in multiple species when increasing the fraction of green from 2 to 41% at about 11% blue. By contrast, multiple studies (including the studies that found no effect of substituting green and red photons) have shown a reduction in leaf area and dry mass gain with an increasing blue photon fraction from 5 to 30% [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Overall, understanding the physiological responses induced by LED lights is a crucial step to regulate plant morphogenesis, enhance the nutritive value of crops, and preserve quality in postharvest fresh products. However, data from the literature are often contradictory because, over the years, many research projects focused their efforts on a few selected species or cultivars, and little is known about the comparison among closed species, more cultivars, or types of the same cultivar [ 22 , 169 , 200 , 201 ]. Eventually, further efforts should be devoted to including harmonized LED metrics and to comparing different light qualities and intensities in the same experimental design.…”
Section: Led Lighting: Advantages and Challenges In Plant Growth Amentioning
confidence: 99%